PEMBERDAYAAN EKONOMI UMAT MELALUI PEMAHAMAN GADAI SYARIAH DI LINGKUNGAN MAJLIS TAKLIM PEKANBARU RIAU - Marina Zulfa; Ficha Melina; Nurul Muyasaroh (Yayasan Wayan Marwan Pulungan, 2026)
This community service activity aims to strengthen community economic empowerment through improving understanding of Islamic pawn (rahn) practices among members of Majlis Taklim at Darussalam Mosque, Tenayan Raya District. The program was implemented using an educational and participatory approach involving lectures, discussions, and practical explanations delivered collaboratively with Islamic bank partners specializing in gold pawn services. The activity was conducted on December 10, 2025, and attended by mosque congregants who actively participated in discussions on sharia-compliant financial solutions. The results show an increase in participants’ knowledge regarding the principles, procedures, and benefits of Islamic pawn schemes as an alternative to conventional financing. Participants also demonstrated greater awareness of the importance of using sharia-based financial products in managing household economic needs. In conclusion, this community service program effectively enhanced financial literacy and contributed to strengthening the economic resilience of the target community through the application of Islamic financial principles.